Pengaruh ROA, ROE, NPM Terhadap Perataan Laba pada Perusahaan Sub Sektor Pertambangan Logam dan Mineral yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021 - Irni Yusnita (CV. ITTC INDONESIA, 2023)
This research was conducted on the official website of the Indonesia Stock Exchange. The research data used by the researcher is the financial statements of the mining sector companies in the metal and mineral mining sub-sector which are listed on the Indonesia Stock Exchange in a row in the 2017-2021 period through the website www.idx.co.id. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique used purposive sampling in order to obtain 25 samples. The analytical method used is multiple linear regression analysis with the help of SPSS. The results of this study indicate that the Return on Assets variable partially has no effect on income smoothing while Net Profit Margin partially affects income smoothing. Then Return on Equity partially has no effect on income smoothing.